A critical update to earlier research findings about the historical roots of gonosen-no-kata – “Forms of post-attack initiative counter throws” (Revista de Artes Marciales Asiáticas, 2024)
The purpose of the present paper is to provide a critical update to previously published findings about the historical background of gonosen-no-kata (“Forms of Post-Attack Initiative Counter Throws”), a non-officially accepted kata of Kodokan judo that achieved some popularity in select European countries. We applied historical methods and source criticism to newly acquired evidence in this way offering a careful critical analysis of this kata’s origin, history and background. Expanding our earlier finding, i.e. the kata’s first verifiable European appearance in London, 1926, from 1927 onward it was spread throughout Europe by a number of judo teachers of Japanese origin. However, the results of this paper now also lead us to firmly refute the caution we had expressed earlier that gonosen-no-kata might well not be of Japanese origin. Indeed, the kata shows up for the first time in November 1915 when it is on display as part of the program surrounding the 20th Waseda University Judo Tournament in Tokyo where it was shown by a pair of judoka, named Nagae and Endo. From then on, the kata was regularly publically demonstrated in Japan at judo contests during the Taisho era (1912-1926) whenever a team from Waseda University participated. Among its most significant early proponents in Japan were Waseda students Endo Moriya, Ninomiya Sotaro, and Yasuoka Toraki. Waseda University’s former chief-instructors Miyakawa Ikkan (1885-1944) and Takahashi Kazuyoshi (1885-1942), and dedicated student(s), such as Endo Moriya (1896-1950) remain the most likely candidates involved in the creation and development of gonosen-no-kata.